Hybrid Moreau's Proximal Algorithms and Convergence Theorems for Minimization Problems in Hilbert Spaces with Applications. (10th December 2018) - Chuang, Chih-Sheng
Abstract: In this paper, motivated by Moreau's proximal algorithm, we give several algorithms and related weak and strong convergence theorems for minimization problems under suitable conditions. These algorithms and convergence theorems are different from the results in the literatures. Besides, we also study algorithms and convergence theorems for the split feasibility problem in real Hilbert spaces. Finally, we give numerical results for our main results.